REKONSTRUKSI MAKNA ISTITHA’AH PADA GENERASI Z DALAM MENUNDA PERKAWINAN:STUDI SOSIOLOGI HUKUM ISLAM DI KECAMATAN SEMEN KABUPATEN KEDIRI - Lilik Mutaharoh; Ulin Na’mah; Husnul Yaqin; Muhammad Ullin Nuha (USRAH: Jurnal Hukum Keluarga Islam, 2026)
This study aims to analyze how Generation Z in Semen District, Kediri Regency, reconstructs the meaning of istitha'ah in their decision to maintain a marriage. The meaning of istitha'ah is not only understood from the biological aspect but are also influenced by economic demands and social changes in society. This empirical legal research uses a qualitative approach, collecting data through in-depth interviews with Generation Z who choose to postpone marriage. The data obtained are explained using the Miles and Huberman model through the stages of data reduction, data presentation, and conclusion drawing. The results show that Generation Z has developed a new understanding of istitha'ah. While previously the ability to marry was more associated with biological readiness, they now consider financial independence and mental maturity as important requirements for marriage. This preparation includes a stable income, the ability to meet household needs, ownership of a residence, and guaranteeing children's future education. Postponing marriage is not seen as a form of ignoring religious advice, but rather as a preventative measure to avoid divorce and marital failure. This study concludes that there is a meeting point between religious values ​​and the realities of modern life in determining standards of readiness for marriage.